Delayed diagnosis of acute ischemic stroke in children – a registry-based study in Switzerland (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY/PRINCIPLES: After arterial ischemic stroke (AIS) an early diagnosis helps preserve treatment options that are no longer available later. Paediatric AIS is difficult to diagnose and often the time to diagnosis exceeds the time window of 6 hours defined for thrombolysis in adults. We investigated the delay from the onset of symptoms to AIS diagnosis in children and potential contributing factors. METHODS: We included children with AIS below 16 years from the population-based Swiss Neuropaediatric Stroke Registry (2000–2006). We evaluated the time between initial medical evaluation for stroke signs/symptoms and diagnosis, risk factors, co-morbidities and imaging findings. RESULTS: A total of 91 children (61 boys), with a median age of 5.3 years (range: 0.2–16.2), were included. The time to diagnosis (by neuro-imaging) was 24 hours in 21 (23%) children. Of 74 children not hospitalised when the stroke occurred, 42% had adequate outpatient management. Delays in diagnosis were attributed to: parents/caregivers (n = 20), physicians of first referral (n = 5) and tertiary care hospitals (n = 8). A co-morbidity hindered timely diagnosis in eight children. No other factors were associated with delay to diagnosis. A total of 17 children were inpatients at AIS onset. CONCLUSIONS:One-third of children with AIS were diagnosed within six hours. Diagnostic delay was predominately caused by insufficient recognition of stroke symptoms. Increased public and expert awareness and immediate access to diagnostic imaging are essential. The ability of parents/caregivers and health professionals to recognise stroke symptoms in a child needs to be improved.